The purple rose of Cairo [videorecording (DVD)] - Allen, Woody, 1935-; Allen, Woody, 1935-; Daniels, Jeff, 1955-; Farrow, Mia, 1945-; Aiello, Danny, 1933-2019 (MGM DVD., 2001)
Cecilia is a poor waitress in a dumpy New Jersey diner who goes to movies to escape the realities of the Depression Era life. Her favorite is "The purple rose of Cairo." When the leading man Tom Baxter decides to be with Cecilia, confusion abounds.